If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 8) + -42 = 5 + -59 Reorder the terms: -4(8 + x) + -42 = 5 + -59 (8 * -4 + x * -4) + -42 = 5 + -59 (-32 + -4x) + -42 = 5 + -59 Reorder the terms: -32 + -42 + -4x = 5 + -59 Combine like terms: -32 + -42 = -74 -74 + -4x = 5 + -59 Combine like terms: 5 + -59 = -54 -74 + -4x = -54 Solving -74 + -4x = -54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '74' to each side of the equation. -74 + 74 + -4x = -54 + 74 Combine like terms: -74 + 74 = 0 0 + -4x = -54 + 74 -4x = -54 + 74 Combine like terms: -54 + 74 = 20 -4x = 20 Divide each side by '-4'. x = -5 Simplifying x = -5
| 2x-y=75 | | 8(y-3)=3y-44 | | 2x^2+16x+24=0 | | X-3y=63 | | 5x+3(x+1)=59 | | 5x-2+3x=59 | | x^2=107 | | 5(x+3)=2 | | 3c^2-14c+8= | | 35+2a=71 | | x-4=x+11 | | 6x^2+25xy+14y^2=0 | | 6x^2+25xy+14y^2+4x-3y-2=0 | | 1,618*x-1,272=0 | | 8x^3-12x^2-2x-1=0 | | x^3-5x^2-10x+48=0 | | 4x^2-10x+8=0 | | 6x^3+4x^2-10x=0 | | x^3+5x^2-10x-48=0 | | 6x^3+4x^2-10x+8=0 | | x^4+6x^3+4x^2-10x+8=0 | | 2y+7=y+8 | | -4*14=x | | -4-14=x | | -[x^2-25x+100]=0 | | -x^2+25x-100=0 | | -x^2-25x-100=0 | | 3x^2+5x+64=0 | | 4a^2-20x+25=0 | | 40x-4=10 | | 10=-4x | | 12x^2-61x+60=0 |